2021
DOI: 10.3389/fgene.2021.727475
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Obesity and Risk of Stroke: A Mendelian Randomisation Analysis

Abstract: Background: The causal relationship between childhood obesity and stroke remains unclear. Our objective was to elucidate the causal relationship between childhood obesity and the risk of stroke and its subtypes by performing Mendelian randomisation (MR) analyses.Methods: Genetic instruments for childhood obesity were obtained from a genome-wide association study (GWAS) of 13,848 European participants. Summary level data for stroke, intracerebral haemorrhage, ischaemic stroke (IS), and its subtypes were evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 47 publications
(64 reference statements)
0
26
0
Order By: Relevance
“…Due to the reduced significance threshold, F statistics were used to evaluate the risk of weak instrument bias, producing a bias level of F <10. Selected SNPs were also matched to databases for phenome-wide association studies (pheWAS) to avoid the potential association between the SNPs and outcomes confounders with a threshold of p < 5 x 10 -6 (26,28).…”
Section: Snp Selectionmentioning
confidence: 99%
“…Due to the reduced significance threshold, F statistics were used to evaluate the risk of weak instrument bias, producing a bias level of F <10. Selected SNPs were also matched to databases for phenome-wide association studies (pheWAS) to avoid the potential association between the SNPs and outcomes confounders with a threshold of p < 5 x 10 -6 (26,28).…”
Section: Snp Selectionmentioning
confidence: 99%
“…As such, we selected SNPs using a less stringent significance of 5 × 10 −6 . This approach has been suggested in previous studies [ 21 , 22 ], with the limitation that it can cause weak instrumental variable bias. We calculated F statistics to assess the risk of such bias and did not find strong evidence of its existence (except for rs9568856 [ F = 9.1367] and rs17697518 [ F = 8.9828], other IVs all showed an F value greater than 10).…”
Section: Discussionmentioning
confidence: 99%
“…When the threshold was set as p < 5 × 10 −8 , only six SNPs could be identified thus failing to meet the minimum requirements for MR studies of at least 10 eligible IVs [ 19 , 20 ]. As such, 15 SNPs were selected using a less stringent threshold of p < 5 × 10 −6 [ 21 , 22 ] and were detected at phenome-wide association studies (pheWAS) catalog databases to identify whether there was a potential association of these SNPs with confounders of outcomes, with a threshold of p < 5 × 10 −6 [ 22 , 23 ]. F statistics were calculated to estimate the sample overlap effect and weak instrument bias considering the relatively relaxed threshold, and an F < 10 was considered dubious bias [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…It has been shown that after the linear regression of each genetic variant on risk factors at p < 1 × 10 −5 as a screening criterion, the results showed the low possibility of weak instrumental variable bias in MR analysis. Therefore, we chose SNPs as IVs associated at this significance level since there were not enough SNPs associated at the genome-wide significant threshold of 5 × 10 −8 [ 27 , 28 ]. Secondly, we used the PhenoScanner tool to ensure whether the IVs were significantly correlated with the risk factors for GDM [ 29 , 30 ].…”
Section: Methodsmentioning
confidence: 99%